2022
DOI: 10.1177/10664807221104126
|View full text |Cite
|
Sign up to set email alerts
|

Couple Relationship Education: Before and During COVID-19

Abstract: The restrictions imposed by the COVID-19 pandemic have required program planners to re-evaluate the provision of relationship education (RE). The current mixed-methods study focuses on the Healthy Relationships [State] initiative's transition from in-person to virtual online RE programing, measuring program impact and comparing the outcomes between the two delivery methods for individuals participating in Couple LINKS, a curriculum designed for adults in committed relationships. Comparisons between delivery me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Second, because interparental conflict was demonstrated to be a risk factor of children's depression, the maintenance of a good marital relationship within a family is paramount. Recent studies have found that couple relationship education programs aimed at teaching couples principles and skills that help them form healthy relationships can yield positive intervention effects on child well-being ( Markman et al, 2022 ; Turner et al, 2022 ). Therefore, to create a good family environment for children, couple relationship education programs can also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because interparental conflict was demonstrated to be a risk factor of children's depression, the maintenance of a good marital relationship within a family is paramount. Recent studies have found that couple relationship education programs aimed at teaching couples principles and skills that help them form healthy relationships can yield positive intervention effects on child well-being ( Markman et al, 2022 ; Turner et al, 2022 ). Therefore, to create a good family environment for children, couple relationship education programs can also be considered.…”
Section: Discussionmentioning
confidence: 99%